Standard operating procedure planning product marketing with participatory ergonomic approach principles - Kasiani, Kasiani; Yusuf, M.; Sarjana, I Made; Kencanawati, Anak Agung Ayu Mirah; Marheni, Lily; Masih, Ni Ketut (International research journal of management, IT and social sciences, 2024)
Candikuning II is part of Baturiti District as a tourism village better known as Bedugul, Bali, Indonesia, and what is no less noteworthy is a range of chips produced by MSME groups as mementos after touring, such as Chips: Spinach; Bean; Tempeh. The goal of this study is to create a Standard Operating Procedure (SOP) for Product Marketing by adopting participatory ergonomic concepts from MSME members. Data collection techniques use observation, documentation, interviews, and Focus Discussion Group. Data analysis techniques using techniques developed by Miles & Huberman, namely analysis including data reduction, data display, and conclusion drawing/verification. The result of this study is the design of Product Marketing SOP by incorporating participatory principles. The conclusion of the study shows that the design of this marketing SOP is considered effective and easy to understand in marketing production products in household industries in Candikuning II Village, Tabanan, Bali.